Optimalisasi Media Saring Zeolite Sebagai Filtrasi Air Sumur dan Edukasi Pada kader Di Desa Temmapaduae Kec Marusu Kab Maros - Annisa Junaid; Alfina Baharuddin; Hardi Hardi; Yuliati Yuliati; Ella Andayanie; Hasriwiani Habo Abbas; Nia Karuniawati (Window of Community Dedication Journal, 2026)
The quality of well water in Temmapaduae Village does not meet health standards. As a result, there are significant health issues. The objective of this community service project is to provide training in water purification techniques. This outreach program consists of five stages: the socialization stage and the implementation stage. This activity comprised three sessions, including: Phase 1: Pre-test, administered via a questionnaire, lectures, Q&A sessions, and discussions; Phase 2: Post-test and evaluation of post-test results; Phase 3: Technology implementation; Phase 4: Monitoring and evaluation; and Phase 5: Program sustainability. The results of the community service activity show: There was a 92% increase in the partners’ knowledge between the pre- and post-tests; there was a 90% increase in the partners’ attitudes between the pre- and post-tests; and there was a 91% increase in the partners’ actions between the pre- and post-tests. Support from the community and local government is needed in the utilization of appropriate technology so that it can be used collectively with other communities that do not yet have water purification filters. It is hoped that the community will maintain the water purification filters and replace the filters used every 3 months